PEMENUHAN GIZI KELUARGA DAN TAMBAHAN PENGHASILAN RUMAH TANGGA MELALUI OPTIMALISASI PEKARANGAN RUMAH DI KELURAHAN KUIN UTARA - Andi Suci Anita; Edward Zubir; Mukhyar Amani (Universitas Islam kalimantan MAB, 2017)
One of the new strategies in increasing food consumption is through the use of yard land. The yard is a plot of land around the house that can be used for the purpose of improving the nutrition of the micro through the improvement of the family menu. In terms of land use, yard is an effort to optimize the use of land because it can be carried out various agricultural activities of high value. However the narrowness of the home yard, if managed properly will produce something of high value. By planting vegetables in your own yard, it is hoped to be one of the best savings solutions by not reducing the nutritional needs of family members. Partners Devotion to the community are housewives housed in the alley Palapa RT. 5 KelurahanKuin Utara North Banjarmasin with a source of household income from fish cracker making business, shrimp crackers, factory workers, carpenters, masons, massage services, selling stalls and fried foods. The location of this service is close to the river basin so it looks shabby and according to the local government of Kuin Utara Village, that the majority of society's income is uncertain every month, then supported by the condition of the yard is still possible to plant so it is suitable to do the PkM UT in this environment. Methods performed on community service are carried out by giving counseling about home garden optimization, vegetable seed distribution, planting medium and shelf arrangement, mentoring and monitoring (evaluation). The purpose of this activity is to optimize the home yard as a source of nutrition of family members and increase household income and increase the knowledge of the community in using the narrow yard with organic vegetables cultivation free of pesticides.